A Bench in Disarray : The Quebec Judiciary and The Federal Department of Justice, 1867-1878 - Swainger, Jonathan (Les Cahiers de droit, 1993)
The poor state of the Quebec judiciary following Confederation was widely recognized although there was no consensus as to the nature of the problems or possible solutions. At issue was not only the quality of the administration of justice but also the philosophical assumptions underlaying George-Etienne Cartier's judicial decentralization act of 1857. Thus despite the efforts of reformers committed to the modernization of Quebec through a rational legal structure, the subsequent relationship between the judiciary and the Department of Justice suggests that intrigue, manipulation, obstruction, and opportunism did more to shape the quality of Quebec's bench prior to 1878.